Caudal paramedian approach to cryptorchidectomy in 29 small ruminants (2011‐2019). Issue 1 (4th December 2020) - Haig, Fallon M.; Baird, Aubrey N.; Hawkins, Jan F.; Moore, George E.
Abstract: Objective: To describe a caudal paramedian approach to cryptorchidectomy in small ruminants. Study design: Retrospective case series. Animals: Sheep (n = 20) and goats (n = 9) with cryptorchidism. Methods: Medical records from January 2011 to July 2019 of small ruminants that underwent caudal paramedian cryptorchidectomy at our institution were retrospectively reviewed. Data from animal signalment, operative and postoperative complications, and client satisfaction were evaluated. Results: Twenty sheep and nine goats underwent caudal paramedian cryptorchidectomy during the study period. The median age of rams was 2 months, and the median age of bucks was 3 months; median weights for rams and bucks were 20.5 kg (range, 14.5‐41.3) and 28.1 kg (range, 12.9‐82), respectively. Cryptorchidism was bilateral in 27.6% (8/29) of cases and unilateral in 72.4% (21/29). Among unilateral cases, 85.7% (18/21) were right sided and 14.3% (3/21) were left sided. Twenty‐four of 29 (82.8%) cases were performed under sedation. One operative complication occurred in a 4‐year‐old 82 kg buck (rate, 3.4% [95% CI: 0.1%–17.2%]). Postoperatively, there were two minor and one major complications (rates, 6.9% [95% CI: 0.8%–22.1%] and 3.4% [95% CI: 0.1%–17.2%], respectively). Long‐term follow‐up (range, 8‐117 months) reports described owner satisfaction and all animals doing well at the time of follow‐up telephone call. Conclusion: Caudal paramedian approach to cryptorchidectomy was safely performed in small ruminants less than 4 months old. Clinical significance: Ease of surgical technique, minimal operative and postoperative complications, and owner satisfaction make this a suitable method for cryptorchidectomy.